2022
DOI: 10.3390/su141912674
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Patterns of Group Collaborative Learning on Fourth-Grade Students’ Creative Thinking in a Digital Artificial Intelligence Course

Abstract: Digital technology plays a unique role in the cultivation of students’ creative thinking, which helps them solve poorly structured problems with effective and original solutions. This study applied collaborative learning in a digital-technology-supported artificial intelligence (AI) course and aimed to explore the impact of collaborative learning on fourth-grade students’ creative thinking. According to whether a leadership role was assigned by a teacher and a final consensus was built in the group, four patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Critical thinking skills can be trained and improved through collaborative experimental or scientific investigation activities [50]. Social interaction among students can support cognitive abilities in building knowledge independently [51]- [53].…”
Section: The Correlation Between Pre-service Teachers' Collaboration ...mentioning
confidence: 99%
“…Critical thinking skills can be trained and improved through collaborative experimental or scientific investigation activities [50]. Social interaction among students can support cognitive abilities in building knowledge independently [51]- [53].…”
Section: The Correlation Between Pre-service Teachers' Collaboration ...mentioning
confidence: 99%
“…which requires students to interact and work together in groups that have a small size, made up to four-members of different level of knowledge [26] [27]. Through group collaborative learning integrated with semantic strategy, students can construct a deeper understanding and reach a consensus [28] [29]. Research has demonstrated that diversity affects the quality of learning in groups.…”
Section: Introductionmentioning
confidence: 99%